BMP-2-Driven Osteogenesis: A Comparative Analysis of Porcine BMSCs and ASCs and the Role of TGF-β and FGF Signaling - Roman Taday; Pascal Jungbluth; Sebastian Zensen; Thomas Krakau; Joachim Windolf; Michèle J. Hoffmann; Vera Grotheer (Biology, 2025)
Mesenchymal stromal cells (MSCs), such as bone marrow-derived cells (BMSCs) and adipose-derived cells (ASCs), are key candidates for bone regeneration therapies but have not yet been integrated into standard clinical practice due to heterogeneity in their osteogenic capacities. This study investigated the osteogenic differentiation of porcine BMSCs and ASCs by analyzing BMP-2-induced receptor expression and the effects of inhibiting BMP, TGF-β, and FGF signaling pathways. While pBMSCs underwent osteogenesis in standard differentiation medium, pASCs required BMP-2 stimulation to initiate this process. BMP signaling inhibition via dorsomorphin suppressed osteogenic differentiation, but this effect was reversed by co-inhibition of TGF-β or FGF signaling. Notably, simultaneous inhibition of TGF-β and FGF in the presence of BMP-2 optimized osteogenic differentiation in both pMSC types. In pASCs, successful differentiation correlated with early activation of p38 MAPK and Wnt signaling pathways, with BMP-2 serving as a primary driver, while TGF-β and FGF pathways acted as modulators. These findings highlight the importance of signaling context and MSC tissue origin in bone formation and suggest that tailored modulation of BMP, TGF-β, and FGF signaling will be necessary in future in vivo applications to maximize the regenerative potential of MSC-based therapies.